Coating anode of perovskite intermediate layer and preparation method and application of coating anode

By preparing ABO3-type perovskite intermediate layer coated anodes on titanium substrates, the problem of easy corrosion of coated titanium anodes in harsh environments was solved, the electrocatalytic performance and lifespan were improved, precious metal waste was reduced, and efficient energy conversion was achieved.

CN119287455APending Publication Date: 2025-01-10JIANGXI STANDE ELECTRODE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411261457.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing coated titanium anodes are prone to corrosion in harsh working environments, leading to coating peeling and decreased conductivity. Furthermore, it is difficult to achieve both high activity and high stability, resulting in significant waste of precious metals.

Method used

An ABO3-type perovskite intermediate layer coated anode was used. Combining the conductivity and stability of perovskite, a dense oxide film was prepared on a titanium substrate by thermal decomposition, which enhanced the adhesion between the coating and the substrate and protected the substrate after the active catalyst layer failed.

Benefits of technology

It improves the electrocatalytic performance and service life of the coated anode, reduces the waste of precious metals, achieves more efficient conversion of chemical energy to electrical energy, and reduces power consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287455A_ABST
    Figure CN119287455A_ABST
Patent Text Reader

Abstract

The invention discloses a coating anode of a perovskite intermediate layer, the surface of the coating anode is usually subjected to oxidation reaction, the coating anode can be applied to the field of electrolytic manufacturing, coating titanium anodes with different purposes are formed according to different coating components, and particularly relates to the coating anode of the perovskite intermediate layer. The electrode needs to be subjected to the working procedures of machining, surface treatment, key middle layer coating, active coating coating and sintering and the like, and the titanium anode capable of achieving different purposes such as electrolytic copper foil production and electrolytic chlorine production is finally obtained. Compared with the design of a traditional anode, the compact oxide film is constructed between the active catalytic layer and the substrate, and the preparation method has the advantages that the preparation method is simple, a thermal decomposition method is used as a basis, complicated and precise equipment is not needed, and the production cost is low; the structure is tightly combined with the base material and the catalyst layer, the adhesion is good, and the actual service life is long; the conductivity is good, the chemical corrosion resistance is high, and the corrosion of electrolyte to a base material is prevented, so that low potential is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to the technical field of electrolytic anodes, and in particular to a coating anode with a perovskite intermediate layer and a preparation method and application thereof. Background Art

[0002] Since the invention of coated titanium anodes, industries involving hydrometallurgy or electrolytic production have begun to use them on a large scale. The electrolytes in these fields are usually strongly acidic or alkaline, so anode materials with strong corrosion resistance, low potential and high product selectivity are required. At present, the electrolytic chlorine industry uses a large number of coated titanium as anodes to produce chlorine and sodium hypochlorite; and with the increasing requirements of current electronic equipment, the electrolytic copper foil industry has gradually shifted from lead anodes to coated titanium anodes. Different reactions will occur during electrolysis depending on the electrolyte, such as oxygen evolution reaction and chlorine evolution reaction.

[0003] However, with the increasing proportion of industrial use and the continuous improvement of industrialization requirements. The working environment of the anode is becoming increasingly harsh (the distance between the cathode and anode is reduced, the anode current density is increased, and the electrolyte flow rate is increased), which causes the corrosive electrolyte to easily pass through the gaps in the active coating and contact the substrate. When the electrolyte reacts with the substrate, the substrate of the coated titanium anode will be passivated to form a dense oxide film, which will lead to problems such as decreased conductivity and coating peeling. Although some people have proposed that Ta2O5 can be used as an intermediate layer to achieve the purpose of transition between the substrate and the active coating, such as the Chinese patent document application number: CN202110989559.1. However, Ta2O5 itself has poor conductivity and no catalytic activity such as oxygen evolution / chlorine evolution. It generally acts as a dispersant and stabilizer in the coating.

[0004] Perovskite is a material with good thermal and chemical stability, which is generally used in related research in the fields of photovoltaics and energy storage. Recently, perovskite, as a material with good conductivity, has been widely used as anode for water splitting to produce oxygen because of its good oxygen evolution reaction activity.

[0005] In view of the problems existing in the above-mentioned coated titanium anode, the present invention combines the advantages of perovskite and the characteristics urgently needed for coated titanium anode, and proposes a coated anode with a perovskite intermediate layer, which not only realizes more efficient chemical energy and electrical energy conversion and achieves the purpose of energy conservation and emission reduction, but also can enhance the bonding strength between the coating and the substrate, reduce the waste of precious metals, and facilitate recycling when scrapped or recoated. Summary of the invention

[0006] In view of the above problems, one of the purposes of the present invention is to provide a coated anode with a perovskite intermediate layer and a preparation method and application thereof, combining the advantages of perovskite and the characteristics urgently needed for a coated titanium anode, and preparing a layer of perovskite between the active precious metal catalytic coating and the inactive substrate, which significantly improves the current problems of poor bonding strength of the anode material coating, short working life, and insufficient electrocatalytic performance.

[0007] At present, coated titanium anodes are generally used in industries that require high-activity electrochemical catalysis, such as copper foil manufacturing, chlor-alkali industry and sewage treatment. However, generally speaking, high activity and high stability are usually not achieved at the same time. Because when an electrochemical reaction is carried out in a solution, only the points where the surface contacts the solution can gain or lose electrons and cause an electrochemical reaction. Highly active anode coatings generally pursue a large specific surface area to reduce power consumption and enhance activity. This means that corrosive electrolytes can easily contact the substrate, resulting in substrate passivation and coating peeling.

[0008] In view of the problems existing in the above-mentioned coated titanium anode, the present invention proposes a coated anode with a perovskite intermediate layer, which not only realizes more efficient chemical energy and electrical energy conversion and achieves the purpose of energy conservation and emission reduction, but also can enhance the bonding force between the coating and the substrate, reduce the waste of precious metals, and facilitate recycling when scrapped or re-coated.

[0009] The technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a perovskite intermediate layer coated anode, comprising a conductive metal substrate and an active coating coated on the surface of the substrate, wherein the active coating comprises at least a bottom perovskite intermediate layer and a surface active coating.

[0010] The main component of the perovskite intermediate layer is an ABO3 type compound, wherein A is one or more of La, Sr, Ca, Ba, Co, Zn or Ti, and B is one or more of Pt, Ag, Au, Ir, Ru, Pd, Rh, Os or Ir.

[0011] Perovskite is composed of an ABO3 structure, and in the present invention, the B position is composed of a noble metal, which provides strong electrochemical stability and corrosion resistance. Therefore, by combining the advantages of perovskite and the characteristics urgently needed by the coated titanium anode, a layer of perovskite is prepared between the active noble metal catalytic coating and the inactive substrate, which significantly improves the current problems of poor coating bonding of anode materials, short working life, and insufficient electrocatalytic performance.

[0012] Since the first coated titanium anode was introduced, people have been thinking that the coated titanium anode should use rutile phase iridium oxide to ensure that its phase is consistent with the titanium substrate. This is because it is easy to think that maintaining the uniformity and consistency of the phase can enhance the bonding between the coating and the substrate.

[0013] As an intermediate layer, the following points must be met: ① First, the density of the intermediate layer structure must be ensured ② The basic structure of titanium must not be destroyed ③ It must be tightly combined with the catalytic layer ④ It must have good electrical conductivity ⑤ It is best to have a certain catalytic activity so that the local resistance will not be too large after the active catalytic layer fails / falls off.

[0014] However, our experiments innovatively found that even if titanium material undergoes high-temperature oxidation above 600°C, there is no loose porous titanium oxide caused by the dissolution of non-metals (N, O, etc.), which further proves the feasibility of the dense perovskite intermediate layer solution. In this application, because the introduction of the perovskite structure does not destroy the structure of the titanium substrate, if a thick layer of titanium oxide is generated on the titanium surface during the sintering process, it will become loose and easy to fall off; if the titanium substrate is directly oxidized and falls off (similar to rust), it will be meaningless.

[0015] The difficulty of this application lies in the fact that the existing technicians have a rigid mindset and believe that the formation temperature of perovskite will affect the bonding ability between the titanium substrate and the catalytic layer. Moreover, the catalytic active material is generally IrO2 (rutile structure), so they would not think of making a layer of perovskite to improve activity / stability.

[0016] Titanium, ruthenium oxide, iridium oxide, etc. will be sintered into rutile structure (this is a structure, MO2, M represents metal) at 400-500 degrees Celsius. In other words, the structures of TiO2 and IrO2 are similar, and they can be combined well. The titanium substrate is the substrate, the perovskite middle layer is the middle layer, and the rutile catalyst layer is the catalyst layer.

[0017] The reason why the present application can generate a dense oxide film structure is due to the nature of the material itself, and it is not affected by human manipulation. This effect can be achieved within the temperature range given in this patent, and this effect cannot be achieved if the temperature is too low or too high. Its main function is to closely combine with the substrate to create a corrosion-resistant intermediate layer, so that even after the catalytic layer falls off, the substrate will not be corroded, thus protecting the coating in other areas. This is because if the substrate is corroded, it is easy to generate TiO2 with poor conductivity, resulting in local failure, and the change in the electric field distribution in this part will increase the current density in other parts, resulting in failure.

[0018] The coated anode of the present invention uses perovskite as an intermediate layer. Compared with a coated titanium electrode without an intermediate layer or with a single Ta2O5 intermediate layer, it has a lower potential and a longer lifespan. It can not only improve the catalytic performance of the overall electrode, but also enhance the bonding force between the active catalytic layer and the substrate.

[0019] Since Ta2O5 has no electrocatalytic activity, it is essentially an inert oxide similar to a semiconductor. The perovskite interlayer containing precious metals has abundant catalytic active sites. Here are a few articles about perovskites: ①A-Site Management Prompts the Dynamic Reconstructed Active Phase ofPerovskite Oxide OER Catalysts; ②Protonated Iridate Nanosheets with a Highly Active and StableLayered Perovskite Framework for Acidic Oxygen Evolution; In general, the intermediate layer will not destroy the structure of the substrate, has good conductivity itself, can form a dense oxide to protect the substrate from corrosion, and has a certain catalytic activity.

[0020] In some achievable embodiments of the first aspect, the perovskite intermediate layer is a dense oxide film; And / or, the thickness of the perovskite intermediate layer is 0.1-1 μm.

[0021] In some achievable embodiments of the first aspect, the active coating is an active oxide in an amorphous or nanoparticle form, and the particle size thereof is in the range of 0.1 to 500 nm.

[0022] It should be noted that amorphous here means that the material has not reached a specific synthesis temperature and has no specific crystal phase. From the perspective of material structure, it is short-range ordered, so it is usually impossible to determine what material it is in characterizations such as X-ray diffraction. Amorphous here means that the morphology has no obvious features, usually manifested as a rough surface.

[0023] Preferably, the thickness of the active coating is 1-20 μm.

[0024] The main purpose of setting the thickness of the active coating at 1-20 μm in the present invention is that the active coating is usually a porous structure or a surface dendrite structure. If the thickness is too small, it will not be able to completely and evenly cover the middle layer, which will cause the activity to be lost in some positions; while if the thickness is too large, the active coating will not be tightly bonded to the middle layer, and the coating will easily fall off, resulting in inactivation.

[0025] In some achievable embodiments of the first aspect, the active coating comprises one or more of Pt, Ag, Au, Ir, Ru, Pd, Rh, Os and Ta (wherein Ta is a non-precious metal); Furthermore, the total content of Ir, Ru or Pt noble metals in the active coating is 2~50 g·m -2For the product itself, only a very low precious metal content is required for operation and production, but its life cannot meet the design requirements. Therefore, under the premise of meeting economic benefits, the total precious metal content is set to 2~50 g·m -2 range.

[0026] In some achievable embodiments of the first aspect, the substrate is a valve-type metal such as titanium, tantalum or niobium, and forms a dense oxide film at an oxidation potential and does not dissolve. If the substrate comes into contact with an electrolyte, it will generate TiO2, which is a semiconductor and has no catalytic activity. At the same time, local oxidation will increase the current distribution of other parts, making it easier to fall off.

[0027] Furthermore, the valve-type metal may be in the form of a plate, a mesh or a tube. The main purpose of using the valve-type metal is to protect the substrate from corrosion and the valve-type metal may be recycled repeatedly.

[0028] In a second aspect, the present invention provides a method for preparing a coated anode of a perovskite intermediate layer, which is used to prepare the coated anode of the perovskite intermediate layer, and the preparation method comprises the following steps: S1: Matrix pretreatment, using sandblasting or shot blasting or mechanical grinding or plasma treatment or electrochemical polishing to make the matrix have a certain degree of roughness, and then use acid etching to remove the oxide layer on the surface of the matrix and increase the specific surface area.

[0029] More preferably, the acid etching solution is one or more of hydrofluoric acid, sulfuric acid, oxalic acid, nitric acid and hydrochloric acid for acid etching; and hydrofluoric acid is added to the acid etching solution.

[0030] By pre-treating the substrate, the substrate surface is made rough, which can better adhere to the intermediate layer and active coating and improve their bonding force (also known as adhesion). The pre-treated substrate is placed in acid for etching, the purpose of which is to remove the oxide film on the substrate surface and form a microscopically irregular surface on the substrate surface, thereby increasing the specific surface area of ​​the substrate. In simple terms, it can make more coating elements adhere per unit area.

[0031] S2: Preparation of the intermediate layer, uniformly coating the bottom perovskite intermediate layer solution on the surface of the substrate, and preparing the perovskite intermediate layer by thermal decomposition. Specifically, the substrate coated with the perovskite intermediate layer solution is placed in a heating furnace for sintering, the sintering temperature is 800-1000 ° C, and the sintering time is greater than 3 min. The above sintering parameters are mainly considered because the perovskite phase needs to be sintered at a temperature of 800-1000 ° C to generate a stable substance, thereby forming a dense intermediate layer structure.

[0032] The preparation method of the bottom perovskite intermediate layer solution is as follows: After the solution containing component A and the solution containing component B are uniformly mixed, a surfactant is added thereto. The surfactant includes but is not limited to polyvinyl pyrrolidone or sodium dodecyl sulfate. The component A is one or more of La, Sr, Ca, Ba, Co, Zn or Ti, and the component B is one or more of Pt, Ag, Au, Ir, Ru, Pd, Rh, Os or Ir.

[0033] It should be emphasized that the two liquids A and B here are homogeneous solutions, as long as they are mixed evenly and no impurities or solvents that cause flocculation or precipitation are added. The main function of the surfactant is to adjust the morphology. After adding the surfactant, a middle layer structure with stable morphology and good density will be obtained.

[0034] S3: Preparation of active coating: The active coating solution of the surface layer is evenly applied to the surface of the semi-finished product with the intermediate layer, and the active coating is prepared by thermal decomposition. Specifically, the substrate coated with the active coating solution of the surface layer is placed in a heating furnace for sintering treatment; the sintering temperature is 440-550 ℃, and the sintering time is greater than 3 minutes.

[0035] Through the above method, it is ensured that the surface of the substrate contains abundant catalytic active sites, and the active coating, the intermediate layer and the substrate are tightly bonded. In addition, the intermediate layer will not have cracks and gaps, ensuring the overall stability of the coated anode.

[0036] In some achievable methods of the second aspect, when the substrate is pretreated by sandblasting, a mixture of one or more of bearing steel sand, brown corundum, and quartz sand with a particle size of 14-24 mesh is used for sandblasting, and the working pressure is 0.4-0.6 MPa; When the substrate is pretreated by shot peening, steel or ceramic shots with a diameter of 0.8-2.0 mm are used, and the working pressure is 0.5-0.8 MPa; When the substrate is pretreated by cathode reduction and electrochemical polishing, the solution used is a mixed solution of one or more of formamide, ethylene glycol, aminosulfonic acid and sodium chloride.

[0037] In some achievable embodiments of the second aspect, the coating method of the perovskite intermediate layer solution and the active coating solution is one or more combinations of roller coating, spraying or sputtering.

[0038] In a third aspect, the present invention provides the use of the above-mentioned perovskite intermediate layer coated anode in the fields of copper foil production, electrolytic chlorine production, water treatment, seawater desalination or printed circuit board manufacturing.

[0039] The oxygen evolution potential of the anode used for copper foil production is less than 1.0 V (vs. MSE); the chlorine evolution potential of the anode used for chlorine production is less than or equal to 1.13 V (vs. SCE).

[0040] (1) The present invention undergoes machining, surface treatment, key intermediate layer coating, and active coating coating and sintering to ultimately obtain a titanium anode that can be used for electrolytic copper foil production, electrolytic chlorine production, and other purposes. Compared with the design of traditional anodes, a dense oxide film is constructed between the active catalyst layer and the substrate.

[0041] (2) The advantages of the present invention are as follows: 1. The preparation method is simple, based on thermal decomposition, does not require complex and sophisticated equipment, and has low production costs; 2. The dense oxide film structure is closely combined with the substrate and the active catalytic coating, with good adhesion and long actual service life; 3. Good electrical conductivity and strong chemical corrosion resistance prevent the electrolyte from corroding the substrate, thus achieving low potential.

[0042] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A schematic diagram of the structure of a titanium anode coated with a perovskite intermediate layer according to an embodiment of the present invention; Figure 2 Schematic diagram of the morphology of the titanium plate in the embodiment of the present invention, the morphology after surface pretreatment, intermediate layer preparation, non-dense intermediate layer comparison and coating preparation, wherein (a) SEM image after surface treatment; (b) SEM image after preparation of dense intermediate layer; (c) SEM image of active coating; (d) SEM image after preparation of active coating; Figure 3 The catalytic performance of the embodiments of the present invention and the comparative examples with and without a perovskite intermediate layer is compared, including (a) the performance comparison of embodiments 1-5 and comparative example 1, and (b) the performance comparison of embodiments 6-10 and comparative example 2. The horizontal axis is the potential and the vertical axis is the current density. The main comparison is the catalytic performance. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0045] Embodiment 1: This embodiment provides a method for preparing a coating anode of a perovskite intermediate layer, and the coating anode is applied to the technical field of copper foil production. The preparation method comprises the following steps: (1) First, a shearing machine was used to cut the sample to size, and the TA1 titanium plate was cut to a size of 100*100 mm.

[0046] (2) The cut titanium substrate was pre-treated by sandblasting using G18 steel sand and a pressure of 0.55 MPa to give the substrate surface a certain degree of roughness.

[0047] (3) Place the pretreated titanium substrate in a 20% hydrochloric acid solution and etch for 30 minutes.

[0048] (4) Prepare a mixed solution of Sr(NO3)2 and H2IrCl6 in a ratio of 1:1 and dissolve the mixture in hydrochloric acid solution to prepare Sr 2+ and Ir 4+ All of them were uniform liquids with a concentration of 10 g / L, and the bottom perovskite intermediate layer solution was obtained.

[0049] (5) Then, the uniform liquid prepared above is evenly applied to the surface of the titanium substrate after acid etching with a brush, and the amount of the coating is 0.25-0.35 g·m -2 The content of Ir element is 0.25-0.35 g per square meter. Specifically, the amount of Ir element applied in this embodiment is 0.3 g·m -2 Element Ir, the content of Ir element per square meter is 0.3 grams. (6) Place the coated wet titanium plate in a muffle furnace and sinter it to 850 °C for 10 minutes at a heating rate of 10 °C / min.

[0050] (7) Repeat steps 5 to 6 three times to obtain a titanium anode semi-finished product containing a perovskite intermediate layer.

[0051] (8) Mix TaCl5 solution and H2IrCl6 solution in a ratio of 3:7 in hydrochloric acid solution to prepare Ir 4+ The mixed solution with a concentration of 100 g / L was used to obtain the active coating solution on the surface.

[0052] (9) The surface active coating solution prepared above is evenly applied to the surface of the titanium anode semi-finished product obtained in step (7) using a brush, with a brushing amount of 1.5-2.5 g·m -2 The content of Ir element is 1.5-2.5 g per square meter. Specifically, the coating amount in this embodiment is 2 g·m -2 The element Ir, that is, the content of Ir element per square meter is 2 grams.

[0053] (10) The coated titanium plate is placed in a muffle furnace and sintered to 500 °C for 5 minutes at a heating rate of 10 °C / min.

[0054] (11) Repeat the above coating and sintering steps ten times until the Ir content reaches 20 g·m -2 , and finally the copper foil anode product is obtained.

[0055] The copper foil anode product provided in this embodiment is Figure 1 As shown, an anode with a sandwich structure is composed of a valve metal substrate, a perovskite intermediate layer, and an active coating containing precious metals. Figure 2 The scanning electron microscope (SEM) images of the intermediate layer and the active coating after surface treatment are shown. From the images, it can be clearly observed that: the substrate after surface treatment ( Figure 2 a) has a rough surface and many tiny pores, which makes it easy to combine with the coating material. Figure 2 b) shows a very dense oxide film that can block corrosion from the electrolyte. Figure 2 d shows the morphology of the active coating, where it can be seen that the precious metal is precipitated in a crystalline manner, enhancing its surface activity.

[0056] In order to verify the effect of different treatment processes on the electrochemical performance, polarization curve (LSV) tests were performed on Examples 1-10 and Comparative Examples 1-2. Figure 3 It can be seen that the activity of Examples 1-5 of the copper foil anode is not much different from that of Comparative Example 1. This is because the activity is mainly provided by the catalytic layer. If the activity is slightly improved, there will be no risk of decline, but the life span will be significantly improved. By comparing the activity of Examples 6-10 with that of Comparative Example 2, it can be found that the activity of Comparative Example 2 without an intermediate layer is lower than that of Examples 6-10 with an intermediate layer. This is because the intermediate layer enhances the bonding between the catalytic layer and the base valve metal, strengthens its conductivity, and ultimately leads to smoother electron transmission and lower potential.

[0057] The anodes prepared in Example 1 and Example 6 are mainly different in application scenarios, so different active precious metal catalytic coatings are used. Examples 1-5 are copper foil anodes, which need to deal with acidic corrosion and acidic oxygen evolution performance, so the catalytic layer generally contains Ir. While Examples 6-10 are chlorine-making anodes, which require corrosion resistance in a neutral or alkaline environment, as well as neutral or alkaline chlorine evolution performance, so the catalytic layer generally contains Ru.

[0058] Example 2: This example provides a copper foil anode, the preparation method of which is basically the same as that of Example 1, except that the Ir in step (8) 4+ The concentration was changed to 80 g / L.

[0059] Example 3: This example relates to a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the coating amount in step (9) is changed to 1.5 g·m -2 The content of element Ir, that is, the content of Ir element per square meter is 1.5 grams.

[0060] Example 4: This example provides a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the acid etching treatment in step (2) is replaced by etching treatment with a mixed acid of hydrochloric acid and hydrofluoric acid.

[0061] Example 5: This example provides a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the hydrochloric acid in step 3 is replaced by oxalic acid and the time is changed to 2 hours.

[0062] Embodiment 6: This embodiment provides an electrolytic chlorine anode, and its preparation method comprises the following steps: (1) First, a shearing machine was used to cut the sample to size, and the TA1 titanium plate was cut to a size of 100*100 mm.

[0063] (2) The cut titanium substrate is sandblasted using G18 steel sand at a pressure of 0.55 MPa to give the substrate surface a certain degree of roughness.

[0064] (3) Place the pretreated titanium substrate in an 18% hydrochloric acid solution and etch for 35 minutes.

[0065] (4) Prepare a mixture of Sr(NO3)2 and H2IrCl6 in a 1:1 ratio and dissolve it in hydrochloric acid solution to make Sr 2+ and Ir 4+ All are uniform liquids at 15 g / L.

[0066] (5) The uniform liquid prepared above is evenly applied to the surface of the titanium substrate after acid etching using a brush, with a brushing amount of 0.20-0.30 g·m -2 The content of Ir element is 0.20-0.30 g per square meter. Specifically, the coating amount in this embodiment is 0.25 g·m -2 Element Ir, that is, the content of Ir element per square meter is 0.25 grams. (6) Place the coated wet titanium plate in a muffle furnace and sinter it to 900 °C for 10 min at a heating rate of 10 °C / min.

[0067] (7) Repeat steps 5 to 6 four times to obtain a titanium anode semi-finished product containing a perovskite intermediate layer.

[0068] (8) Mix RuCl3 solution and H2IrCl6 solution in a ratio of 2:1 in n-butanol solution to prepare Ru 3+ A mixed solution with a concentration of 10 g / L was obtained to obtain an active coating solution on the surface.

[0069] (9) The surface active coating solution prepared above is evenly applied to the titanium anode semi-finished product obtained in step (7) using a brush, with a coating amount of 0.6-0.8 g·m -2 The content of element Ru, that is, the content of element Ru per square meter is 0.6-0.8 grams. Specifically, the amount of Ru applied in this embodiment is 0.7 g·m -2 The element Ru, that is, the content of Ru element per square meter is 0.7 grams.

[0070] (10) Place the coated titanium plate in a muffle furnace and sinter it to 500°C for 5 minutes at a heating rate of 10°C min. -1 .

[0071] (11) Repeat steps 9 to 10 ten times until the Ru content reaches 7 g cm -2 , and finally obtain the anode product of electrolytic chlorine production.

[0072] Example 7: This example provides an electrolytic chlorine anode, and its preparation method is basically the same as that of Example 6, except that the Ru in step (8) 4+ The concentration was changed to 15 g / L.

[0073] Example 8: This example provides an electrolytic chlorine anode, the preparation method of which is basically the same as that of Example 6, except that the coating amount in step (9) is 0.6 g·m -2 The element Ru, that is, the content of Ru element per square meter is 0.6 grams.

[0074] Example 9: This example provides an electrolytic chlorine anode, and its preparation method is basically the same as that of Example 6, except that the acid etching treatment in step (2) is replaced by etching treatment with a mixed acid of hydrochloric acid and hydrofluoric acid.

[0075] Example 10: This example provides an electrolytic chlorine anode, and its preparation method is basically the same as that of Example 6, except that the hydrochloric acid in step (3) is replaced by oxalic acid and the time is changed to 2 hours.

[0076] Example 11: This example provides a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. Sr(NO3)2 and H2IrCl6 are prepared in a ratio of 1:1.2 and dissolved in a hydrochloric acid solution to prepare La 2+ It is a homogeneous liquid of 15 g / L.

[0077] Example 12: This example provides a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. Ba(NO3)2 and H2PtCl6 are prepared in a ratio of 2:3 and dissolved in a hydrochloric acid solution to prepare Ba 2+ It is a homogeneous liquid of 12 g / L.

[0078] Example 13: This example provides a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. Ca(NO3)2 and RuCl3 are prepared in a ratio of 1:1 and dissolved in a hydrochloric acid solution to prepare Ca 2+ It is a homogeneous liquid of 12 g / L.

[0079] Example 14: This example provides a copper foil anode, and its preparation method is basically the same as that of Example 1, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. La(NO3)2 and H2AuCl6 are prepared in a ratio of 1:1 and dissolved in a hydrochloric acid solution to prepare a uniform liquid with a La content of 15 g / L.

[0080] Example 15: This example provides an electrolytic chlorine anode, and its preparation method is basically the same as that of Example 6, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. La(NO3)2 and H2IrCl6 are prepared in a ratio of 1:1.2 and dissolved in a hydrochloric acid solution to prepare La 2+ It is a homogeneous liquid of 15 g / L.

[0081] Example 16: This example provides an electrolytic chlorine anode, and its preparation method is basically the same as that of Example 6, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. Ba(NO3)2 and H2PtCl6 are prepared in a ratio of 2:3 and dissolved in a hydrochloric acid solution to prepare Ba 2+ It is a homogeneous liquid of 12 g / L.

[0082] Example 17: This example provides an electrolytic chlorine anode, and its preparation method is basically the same as that of Example 6, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. Ca(NO3)2 and RuCl3 are prepared in a ratio of 1:1 and dissolved in a hydrochloric acid solution to prepare Ca 2+ It is a homogeneous liquid of 12 g / L.

[0083] Example 18: This example provides an electrolytic chlorine anode, and its preparation method is basically the same as that of Example 6, except that the composition and proportion of the bottom perovskite intermediate layer solution in step (4) are different. La(NO3)2 and H2AuCl6 are prepared in a ratio of 1:1 and dissolved in a hydrochloric acid solution to prepare La 2+ It is a homogeneous liquid of 15 g / L.

[0084] Comparative Example 1: The comparative example provides a copper foil anode, and its preparation method is basically the same as that of Example 1, except that steps 4 to 7 are omitted, that is, a titanium anode without an intermediate layer is prepared.

[0085] Comparative Example 2: The comparative example provides an anode for electrolytic chlorine production, and its preparation method is basically the same as that of Example 6, except that steps 4 to 7 are omitted, that is, a titanium anode without an intermediate layer.

[0086] Table 1 Performance comparison of Examples 1-18 and Comparative Examples 1-2 Sample code Changes compared to Example 1 Lifespan in sulfuric acid (h) Lifespan in 2M NaCl (h) Example 1 Copper Foil Anode Example 1050 / Example 2 Changing the precious metal concentration 999 / Example 3 Change the amount of metal applied per time 980 / Example 4 Change surface treatment 980 / Example 5 Change surface treatment 1024 / Example 6 Electrolytic chlorine anode embodiment / 403 Example 7 Change the precious metal concentration / 402 Example 8 Change the amount of metal applied per time / 420 Example 9 Change surface treatment / 395 Example 10 Change surface treatment / 380 Embodiment 11 Change the middle layer material 1033 / Example 12 Change the middle layer material 995 / Embodiment 13 Change the middle layer material 956 / Embodiment 14 Change the middle layer material 979 / Embodiment 15 Change the middle layer material / 385 Example 16 Change the middle layer material / 410 Embodiment 17 Change the middle layer material / 421 Embodiment 18 Change the middle layer material / 399 Comparative Example 1 Copper foil anode without intermediate layer 410 / Comparative Example 2 Anode for electrolytic chlorine production without intermediate layer / 195 The test conditions in Table 1 above are: 50 kA / m 2 Life test was carried out in 20% sulfuric acid at a constant temperature of 50°C in water at a current density of 20kA / m 2 The life test was carried out in 2M NaCl at a current density of 55°C in a water bath, and the electrolyte was replaced every 48 h.

[0087] By analyzing Table 1 and comparing Examples 1-5 with Comparative Example 1, it can be found that within the scope provided by the present invention, adjusting or changing the process parameters will not have a significant effect on the lifespan, while the copper foil anode without an intermediate layer has less than half the lifespan, which fully demonstrates the advantage of the perovskite intermediate layer.

[0088] By comparing Examples 6-10 with Comparative Example 2, it can be found that, similarly, within the scope provided by the present invention, that is, as long as the chlorine-producing anode using the perovskite intermediate layer is used, the life span is significantly improved, which indicates that the dense perovskite intermediate layer can prevent the erosion of the electrolyte during use.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0090] The above is an exemplary description of the present invention in combination with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as such non-substantial improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A coating anode with a perovskite intermediate layer, characterized in that: It comprises a substrate and an active coating coated on the surface of the substrate, wherein the active coating comprises at least a bottom perovskite intermediate layer and a surface active coating; The main component of the perovskite intermediate layer is an ABO3 type compound, wherein A is one or more of La, Sr, Ca, Ba, Co, Zn or Ti, and B is one or more of Pt, Ag, Au, Ir, Ru, Pd, Rh, Os or Ir.

2. The coated anode of the perovskite intermediate layer according to claim 1, characterized in that The perovskite middle layer is a dense oxide film; And / or, the thickness of the perovskite intermediate layer is 0.1-1 μm.

3. The coated anode of the perovskite intermediate layer according to claim 1, characterized in that The active coating is an active oxide in the form of amorphous or nanoparticles, and its particle size is in the range of 0.1 to 500 nm; And / or, the thickness of the active coating is 1-20 μm.

4. The coated anode of the perovskite intermediate layer according to claim 1, characterized in that The active coating comprises one or more of Pt, Ag, Au, Ir, Ru, Pd, Rh, Os and Ta; And / or, the total content of Ir, Ru or Pt noble metals in the active coating is 2-50 g / m 2 .

5. The coated anode of the perovskite intermediate layer according to claim 1, characterized in that The substrate is a valve-type metal selected from titanium, tantalum or niobium, and forms a dense oxide film at an oxidation potential without dissolving; And / or, the valve-type metal is in the form of a plate, a mesh or a tube.

6. A method for preparing a coating anode with a perovskite intermediate layer, characterized in that: A coating anode for preparing a perovskite intermediate layer according to any one of claims 1 to 5, the preparation method comprising the following steps: S1: substrate pretreatment, using sandblasting or shot blasting or mechanical grinding or plasma treatment or electrochemical polishing to make the substrate have a certain degree of roughness, and then using acid etching to remove the oxide layer on the substrate surface and increase the specific surface area; S2: intermediate layer preparation, the bottom perovskite intermediate layer solution is evenly coated on the substrate surface, and the perovskite intermediate layer is prepared by thermal decomposition method; S3: Preparation of active coating: The active coating solution of the surface layer is evenly coated on the surface of the semi-finished product with the intermediate layer, and the active coating is prepared by thermal decomposition method.

7. The method for preparing a coating anode of a perovskite intermediate layer according to claim 6, characterized in that: The method for preparing the bottom perovskite intermediate layer solution in step S2 is to uniformly mix the solution containing component A and the solution containing component B, and then add a surfactant thereto; And / or, the surfactant includes but is not limited to polyvinyl pyrrolidone or sodium dodecyl sulfate.

8. The method for preparing a coating anode of a perovskite intermediate layer according to claim 6, characterized in that: When the substrate is pretreated by sandblasting, one or more of 14-24 mesh bearing steel sand, brown corundum, and quartz sand are mixed for sandblasting, and the working pressure is 0.4-0.6 MPa; And / or, when the substrate is pretreated by shot peening, steel shot or ceramic shot with a diameter of 0.8-2.0 mm is used, and the working pressure is 0.5-0.8 MPa; And / or, when the substrate is pretreated by cathode reduction and electrochemical polishing, the solution used is a mixed solution of one or more of formamide, ethylene glycol, aminosulfonic acid, and sodium chloride; And / or, the acid etching solution is one or more of hydrofluoric acid, sulfuric acid, oxalic acid, nitric acid and hydrochloric acid for acid etching; And / or, hydrofluoric acid is added to the acid etching solution.

9. The method for preparing a coating anode of a perovskite intermediate layer according to any one of claims 6 to 8, characterized in that: The thermal decomposition method comprises the steps of placing the substrate coated with the perovskite intermediate layer solution or the surface active coating solution into a heating furnace for sintering treatment; and / or, the sintering temperature of the perovskite intermediate layer is 800-1000° C., and the sintering time is greater than 3 min; And / or, the sintering temperature of the active coating is 440-550°C, and the sintering time is greater than 3 min; And / or, the coating method of the perovskite intermediate layer solution and the active coating solution is one or more combinations of roller coating, spraying or sputtering.

10. Use of the coating anode of the perovskite intermediate layer according to any one of claims 1 to 5 in the fields of copper foil production, electrolytic chlorine production, water treatment, seawater desalination or printed circuit board manufacturing.

Citation Information

Patent Citations

  • A long-life titanium-based tin oxide anode, its preparation method and application

    CN113718201B